ANALISIS KANDUNGAN POLIFENOL DALAM RUMPUT LAUT Sargassum sp DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Pirman AP; Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2009)
Seaweed are one of resource foreign exchange of state and earning source for coastal area society. Besides can be used direct upon which food, some result processing of seaweed like gelatinous, carrageenan and alginate represent the compound which important enough in industry. A lot of research proving that seaweedis substance of food which important, like some among other thing is anticancer, antioxidant, preventing kardiovaskular, and as diet food. As for content of chemistry compound anticipated by a sharing to cause the effect is compound polyphenol. Referring to above the mentioned, and to know furthermore hit the content polyphenol in Sargassum sp seaweed, is hence done by analysis research polyphenol in Sargassum sp seaweed. This research benefit is to give the erudite evidence and information about existence of content polyphenol of Sargassum sp seaweed. This research is done by using method of spectrofotometric UV-Visibel and as reagent used by Folin Ciocalteu and Na2CO3 yield the blue colour, then read by absorbance at 670 nm. As standard condensation used by tannat acid with the concentration 0,25; 0,5; 1,0; 2,0; 4,0; and 8,0 ppm. From research result indicate that the Sargassum sp seaweed contain the polyphenol with the rate polyphenol of Sargassum sp I as much 0,077 mg/100 g and Sargassum sp II as much 0,071mg/100 g.Key Words : Polifenol, Sargassum sp, Spectrofotometric UV-Vis